The Effectiveness of Health Education Intervention to Promote Breast Self- Examination Practice: A Systematic Review - Myint, Nyein Moh Moh; Nursalam, Nursalam; Has, Eka Mishbahatul M (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer is the most common cancer and one of the causes of the highest mortality in women. Early detection and screening are essential to reduce the mortality rate of breast cancer. Breast self-examination is one of the screening methods to get an early diagnosis. It can help to diagnose 95% of all breast cancers in the primary stage. To explore the most effective method of health interventions to promote BSE practice from international studies, the authors searched articles in four databases; EBSCO, ScienceDirect, Scopus and ProQuest between 2016 and 2020. Any experimental research that evaluated the effectiveness of health education regarding breast self-examination, any age of women from any countries and articles written in English were considered as the inclusion criteria. Seventeen articles that met inclusion criteria were chosen for this review. Based on the findings, the authors divided into two methods: face-to-face health education (educational and practical session, group discussion and role play) and indirect health education based on information and communication technology (text messaging, mobile-based application). Each education method showed positive effects. If the technology combined with face-to-face health education method, the better outcomes were seen. The reminder should also add in these methods for long-term practice.